Relasi Tuhan Dan Manusia (Refleksi Platonis atas Hinduisme) - Muliadi Muliadi (UIN Sunan Gunung Djati Bandung, 2017)
This article discusses the relationship of God and man in view of Hinduism. The paradigm used in this reflection is the Plato's metaphysics about relatinships pattern of Idea and reality. View of Hinduism, Brahman is the highest Idea that must be addressed by all human beings. To make it easier to understand God or Brahman, in Hinduism there is the understanding that God manifests itself in various forms of gods and goddesses. Man in view of Hinduism, has same elements with the universe as the manifestation of God, then to recognize God, man can also through the understanding of human identity that is Atman. Hinduism teaches various ways or methods to serve and understand God, including of it: bhakti yoga, karma yoga, jnana yoga and raja yoga. In this life, humans are bounded by responsibility. If it’s actions or works are good, so humans will find good result, but if the evil that is done, then humans will get karma. Karma is what prevented him to merge with Brahman / Atman, so that human life will undergo a series or sequence of rebirth, even in the form of lower called samsara. To break this samsara, people should stay away from the mirage of life, do the good, and be aware or understand of their identity that blends with nature is that while blending with the Almighty or moksha.